Ecological and forestry assessment of the compliance of the composition of forest crops designed for afforestation with the types of forest site conditions in the Steppe climate of Ukraine - Svitlana Raspopina; Anastasiia Suska; Yulia Belay; Vitalii Goroshko (Наукові праці Лісівничої академії наук України)
The dynamics of afforestation (over the last twenty years) in Ukraine and the indicators of survival and preservation of 1–3-year-old forest crops in the steppe regions (according to the data of the State Agency of Forest Resources of Ukraine) were analyzed. It is shown that particularly low rates of preservation of woody plants are characteristic of forest crops created during afforestation in forestry enterprises of Dnipropetrovsk, Donetsk, Mykolaiv, Kherson and Zaporizhya regions. The main cause of low survival rates and preservation of crops is drought. In particular, in Dnipropetrovsk region over the last five years, the actual average survival rate of forest crops did not exceed 41 %, which is 1.7 times lower than the standard indicator (70%). The dominant cause of forest crops mortality (97.3% of cases), as in other steppe areas, is drought. The projects for the creation of forest crops at the Branch «Petrikivske Forestry» of the State Specialized Forest Enterprise «Forests of Ukraine» (Dnipropetrovsk region) for the year 2023 were analyzed from the point of view of the compliance of the composition of the projected forest crops with the existing types of forest site conditions. A study of the dynamics of the temperature regime in Dnepropetrovsk region for the period 2010–2023 showed that during the most active growing season (from May to September), extremely high temperatures last for an average of 47 days. Moreover, the average number of days with temperature from 30 to 35° C is 35, and with temperatures of 35–40°C is 12 days. Considering the low viability of forest crops created during afforestation, as well as the tendency towards increased drought, ways to optimize the composition of forest crops have been proposed. Forestry enterprises in the conditions of the steppe climate, which are focused on the creation of protective, recreational, sanitary and other forest stands, are recommended to use more widely drought-resistant broad-leaved species, the seedlings of which are more resistant than conifers to long periods of high temperatures. For example, it is recommended to use Robinia pseudoacacia more widely in dry relatively fertile forest site conditions (FSC – C1) and in realtively infertile conditions (В1) (except for lowland relief elements). In dry relatively fertile or fertile forest site conditions (C1, D1), Quercus robur should be supplemented with Prunus armeniaca and Morus alba, which exhibit high drought and heat resistance. It is advisable to limit the use of Рinus sylvestris, giving preference to Pinus pallasiana, whose sprouts, seedlings, and elder trees are more resistant to drought, insect pests and pathogens. In very dry infertile forest site conditions (В0), an alternative to forest plantations should be shrubby vegetation.